Committee on the Status of Minority Groups in the Economics Profession (CSMGEP) - Rouse, Cecilia Elena; Hoover, Gary A. (American Economic Review, 2017)
Report: Committee on the Status of Minority Groups in the Economics Profession (CSMGEP) by Cecilia Rouse and Gary A. Hoover. Published in volume 107, issue 5, pages 777-91 of American Economic Review, May 2017